건강환경 조성을 위한 주의회복이론 관점의 치유환경 고찰 - 청계천을 중심으로 - 김무한; Kim Moohan (한국조경학회지, 2017)
최근 대체 의학에 대한 관심과 함께 일상적인 공간과 활동을 통한 건강증진에 많은 관심이 일고 있다. 이에 본 연구는 치유환경에 대한 물리적 공간의 효용가치와 구체적인 공간 유형별 차이에 관해 다룸으로 근거중심디자인 관점에서 조경계획 및 설계단계에 유용한 결과를 도출하고자 한다. 이를 위해서 인위적으로 조성된 조경공간의 치유효과가 얼마나 있는지에 대한 평가가 요구되며, 구체적인 공간에 대한 평가가 요구된다. 본 연구는 청계천 1.5km 구간을 대상으로 주의회복 효과와 공간 유형에 대해 논하고자 한다. 연구 방법으로는 공간에 대한 해석과 주의회복환경 정도를 묻기 위한 회복환경지각척도를 활용하였다. 연구결과는 다음과 같다. 첫째, 청계천 조사 구간의 평균 회복환경지각척도는 6.12로 도출되었다. 이는 선행 연구를 기준으로 옥상 정원이나 언덕 그리고 정원에 비해서는 높은 수치이고, 자연호수가 주는 주의회복효용정도와 유사한 값을 보였다. 둘째, 공간 유형에 따른 차이를 확인하기 위해 각 5개 공간 유형별로 ANOVA 분석을 실시하였는데, 그 결과로 안쪽 경계부 공간 유형이 치유효과가 높게 나타났다. 이상의 결과는 조경공간의 치유효과에 대한 근거자료가 되며, 세부 공간 유형 설계 시 치유공간 설계에 참고가 될 것으로 기대된다. With the recent increasing interest in preventive medicine, observation has been made regarding the positive relationship between a routinized place that includes activity and health improvement. This study evaluates the effective value of a designed landscape for seeing a healing environment and sees the difference of the effective value of classified physical settings regarding Evidence Based Design. Therefore, the study evaluates the perceived restorativeness scale of Cheonggyceheon`s 1.5km section and five type settings in the same section regarding how much it works as a healthy urban park. The research methodology used to study sub-settings` and the research site`s restoration effects was observation and questionnaires. A PRS (Perceived Restorativeness Scale) questionnaire survey was the research tool employed. The study drew two major results. Firstly, PRS 6.12 is the score of the whole research site, so the study identifies that Cheonggycheon has a mental fatigue restoration function. Secondly, the sub-setting named `Near Sidewall` was the most attention restorative, according to the ANOVA results. In conclusion, this study suggests significant information support regarding the reasons for creating green areas in urban settings by identifying a particular designed healing sit.